Spaces of Commoning. Artistic Research and the Utopia of the Everyday - Gruber, Stefan; Miller, Vladimir; Verlič, Mara; Wang, Hong-Kai; Wieger, Julia; Baldauf, Anette; Hille, Moira; Krauss, Annette (Publication Series of the Academy of Fine Arts Vienna, 2016)
In the context of major economic crises, ecological catastrophes and pervasive technological innovations, the commons have resurfaced as a key concept in the discussions of alternative economies, new social movements and the transformation of public space; the debate promises to provide new entry points for a radical repudiation of neoliberal politics and the envisioning of alternatives beyond capitalism. This edited volume is one of the outcomes of the research project "Spaces of Commoning", whose major goal is to investigate where and how the creative insights and energies developed in and around the commons debate can contribute to challenge prevalent concepts of public space, that tend to linger in the naïve belief that the state and market work in opposition. Ironically, in the course of their vast proliferation in recent years, commons have provided not only a new entry point to anti-capitalist critique and activism, they are now also used as a force of economic growth. In other words, capital is promoting the commons in its own way. The pervasive spread of forms of secluded living, but also exclusive variations of educational, health or food commoning indicate how smoothly the alternative value systems of the commons is integrated into the workings of capitalism. Can this old idea of the commons still provide a new strategy to disrupt capitalist appropriations and ever accelerating cycles of gentrification? Can it help us to articulate and bring together the many existing struggles that currently recognize the power to challenge the mantra of capitalist accumulation and profit-driven growth?